2020
DOI: 10.1021/acs.bioconjchem.0c00240
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Corona Does Not Influence Receptor-Mediated Targeting of Virus-like Particles

Abstract: Protein corona formation has been regarded as an obstacle to developing diagnostic and therapeutic nanoparticles for in vivo applications. Serum proteins that assemble around nanoparticles can hinder their targeting efficiency. Virus-based nanoparticles should be naturally predisposed to evade such barriers in host organisms. Here, we demonstrate that virus-like particles derived from mouse polyomavirus do not form a rich protein corona. These particles can be efficiently targeted to cells that overproduce tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 107 publications
(174 reference statements)
0
12
0
Order By: Relevance
“…98 Recently, researchers identified that the ability of polyomavirus-based VLPs to engage their target receptors was not affected by the protein corona. 99 These VLPs maintained target specificity and were internalized into cancer cells via clathrin-dependent endocytosis in the presence of human serum. These findings fit with the idea that viruses have evolved mechanisms of immune avoidance that ameliorate their ability to deliver enclosed genetic material.…”
Section: Nanoparticles As a Platform For Immunomodulationmentioning
confidence: 99%
See 1 more Smart Citation
“…98 Recently, researchers identified that the ability of polyomavirus-based VLPs to engage their target receptors was not affected by the protein corona. 99 These VLPs maintained target specificity and were internalized into cancer cells via clathrin-dependent endocytosis in the presence of human serum. These findings fit with the idea that viruses have evolved mechanisms of immune avoidance that ameliorate their ability to deliver enclosed genetic material.…”
Section: Nanoparticles As a Platform For Immunomodulationmentioning
confidence: 99%
“…The findings of Alam et al are particularly interesting because VLP-based vaccine platforms may circumvent challenges associated with protein corona formation such as interfering with targeting . Recently, researchers identified that the ability of polyomavirus-based VLPs to engage their target receptors was not affected by the protein corona . These VLPs maintained target specificity and were internalized into cancer cells via clathrin-dependent endocytosis in the presence of human serum.…”
Section: Nanoparticles As a Platform For Immunomodulationmentioning
confidence: 99%
“…VLPs inherit the advantages of proteins and can be genetically modified with targeting peptides, whereas inorganic nanoparticles are generally modified with the targeting ligands through direct chemical coupling or through the use of organic polymer linkers [ 150 ]. In addition, studies have shown that the targeting ability of VLPs will not be adversely affected by protein corona [ 151 ]. However, when silica was modified with transferrin, the protein corona formed on the surface of silica would shield transferrin, making it lose the ability to bind with transferrin receptors.…”
Section: Cancer Therapy By Using Protein Nanoparticlesmentioning
confidence: 99%
“…The formation of serum PCs around NPs is generally considered to hinder the targeting efficiency of NPs. In the case of serum proteins coated with transferrin (Tf) functionalized virus-like particles, recent studies have indicated that they can successfully target cancer cells with transferrin receptors via the covalent coupling of Tf molecules on the capsid surface, i.e., the PCs have no effect on their uptake into tumor cells [133]. Tuning PCs by modulating the surface chemistry of NPs opens up great potential for the regulation of the non-specific cellular uptake of NP-PC complexes and for improving the therapeutic efficacy of nanomedicines.…”
Section: Regulating Cellular Uptake and Improving Drug Deliverymentioning
confidence: 99%
“…successfully target cancer cells with transferrin receptors via the covalent coupling of Tf molecules on the capsid surface, i.e., the PCs have no effect on their uptake into tumor cells [133]. Tuning PCs by modulating the surface chemistry of NPs opens up great potential for the regulation of the nonspecific cellular uptake of NP-PC complexes and for improving the therapeutic efficacy of nanomedicines.…”
Section: Regulating Cellular Uptake and Improving Drug Deliverymentioning
confidence: 99%